“Eating Daintily”: Food and Social Practices in the Danubian Principalities (1780-1850) - Vintilă, Constanţa (Food & History, 2023)
Abstract This article analyses the relations between food, social status and the circulation of knowledge in south-eastern Europe. During the long eighteenth century, the mobility of people led to the circulation of culinary practices and information regarding the organization of meals and the spread of good manners. With the help of ego-documents, travel narratives and private archives I examine how the Christian elites in the Ottoman Empire adapted to the flux of new practices and fashions diffused through the intermediary of people, objects, gazettes and books. Together with recipes and new sorts of food, a whole set of utensils was borrowed and adapted to meet the new requirements. The civilizing process was long and difficult, and documentary and visual sources capture very well the delay between the circulation of objects and information, on the one hand, and their assimilation in the nineteenth century, through the generation of the revolutions, on the other Résumé Mon étude analyse la relation entre la nourriture, le statut social et la circulation du savoir à travers le Sud-Est de l’Europe. La mobilité des gens aboutit à la circulation des pratiques culinaires et des informations sur l’organisation des mets et des bonnes mœurs. À l’aide d’ego-documents, de narrations de voyage et d’archives privées, j’examine comment les élites chrétiennes de l’Empire ottoman s’adaptent aux nouvelles pratiques culinaires et sociales par l’intermédiaire de multiples rencontres avec des gens, des objets, des magasins ou des livres. Avec les recettes et les nouveaux plats, divers outils ont été acquis pour accomplir les tendances à la mode. Le processus de civilisation a toutefois été long et difficile, et les sources écrites et visuelles saisissent bien d’une part, le décalage entre la circulation de l’information et de l’objet et, d’autre part, leur assimilation tout au long du XIXe siècle
Keywords: Food